Praktik Taruhan Kecil dalam Pertandingan Sepak Bola: Analisis Tafsir Ayat Larangan Maysir (QS. al-Māidah Ayat 90-91) dan Implikasinya terhadap Moralitas Penggemar Muslim - M. Ariq Fadhil Shabri; Husnel Anwar Matondang (Aksioreligia, 2026)
This study examines the practice of small-scale betting in football matches among Muslim supporters by analyzing the interpretation of Qur’an Surah Al-Māidah verses 90–91 on the prohibition of maysir. The study is motivated by the widespread assumption that minor betting in football and futsal games is merely entertainment and does not constitute serious gambling. This research aims to analyze the forms, motives, and moral implications of small-scale betting from the perspective of Qur’anic interpretation. The study uses a qualitative method with a descriptive-analytical approach through interviews with six Muslim informants who had experience participating in betting during football matches. The findings show that betting practices are influenced by economic motives, entertainment, peer influence, and the desire to increase enthusiasm during games. However, these practices also generate negative impacts, including conflict, emotional tension, declining sportsmanship, and feelings of guilt. Based on the interpretations of Ibn Kathir, Ath-Tabari, and Quraish Shihab, all forms of gambling, including small-scale betting, are categorized as maysir because they contain speculation and unlawful gain. Therefore, small-scale betting in football matches contradicts Islamic values and contributes to the decline of Muslim moral conduct.